Analisis Simulasi Distribusi Logistik Menggunakan Metode Transportasi - Cahya Purnomo; Vivid Dekanawati; Ningrum Astriawati; Sumardi Sumardi; Ganda Syahputra (SAINTARA, 2022)
Transportation problems are generally related to logistics distribution from several sources of products with limited capacity to several destinations that require certain quantities to be optimal. Study aim to analize optimum logistics distribution.Methode by simulation data of factory with certain capacity to 4 warehouse with certain requirement. The factories and warehouses are located in different locations and transportation costs from each factory to each destination is different. Initial solution by Least Cost Method, then optimization use MODI method. The results of the two simple transportation methods are proven to be able to show distribution optimization, by reduce cost 8,43 %.